2014
DOI: 10.1242/dev.106914
|View full text |Cite
|
Sign up to set email alerts
|

The cortical hem regulates the size and patterning of neocortex

Abstract: The cortical hem, a source of Wingless-related (WNT) and bone morphogenetic protein (BMP) signaling in the dorsomedial telencephalon, is the embryonic organizer for the hippocampus. Whether the hem is a major regulator of cortical patterning outside the hippocampus has not been investigated. We examined regional organization across the entire cerebral cortex in mice genetically engineered to lack the hem. Indicating that the hem regulates dorsoventral patterning in the cortical hemisphere, the neocortex, parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 88 publications
1
75
0
Order By: Relevance
“…Cortical size and patterning depends upon Wnts secreted by the medially-situated cortical hem [34]. We thus asked whether the hem (in which the Emx1-Cre transgene is active; [25, 34]) might be disrupted in the absence of Akirin2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cortical size and patterning depends upon Wnts secreted by the medially-situated cortical hem [34]. We thus asked whether the hem (in which the Emx1-Cre transgene is active; [25, 34]) might be disrupted in the absence of Akirin2 .…”
Section: Resultsmentioning
confidence: 99%
“…We thus asked whether the hem (in which the Emx1-Cre transgene is active; [25, 34]) might be disrupted in the absence of Akirin2 . In situ hybridization suggested that this, indeed, was the case, as strong expression of hem markers Wnt3a (E10.5 and E11, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our data suggest a novel mechanism in which the interaction of γ-Pcdh-C3 with Axin1 can potentially sequester it away from other Wnt signaling components, which leads to Lrp6 hypophosphorylation and reduced Wnt target gene expression through an as-yet undetermined pathway. It is likely that γ-Pcdhs act as modulators or buffers for Wnt signaling activity, rather than as primary co-factors, as a grossly normal cerebral cortex still forms in mice overexpressing γ-Pcdh-C3 or –A1 [204]; major disruption of Wnt signaling in embryonic telencephalon (e.g., through ablation of the Wnt-producing cortical hem; [205]) leads to a severe disruption of cortical development. As it stands, it will be important to determine if any of the many roles that γ-Pcdhs play in the brain are dependent on its modulation of Wnt pathways.…”
Section: Regulation Of Wnt Signaling By Pcdhsmentioning
confidence: 99%
“…The cortical hem is the embryonic organizer for the hippocampus and a major regulator of cortical patterning outside the hippocampus. It provides a source of Winglessrelated (WNT) and bone morphogenetic protein (BMP) signaling in the dorsomedial telencephalon to control proper cortical regionalization and NPC expansion in a paracrine fashion (15,16). Thus, the severe patterning and arealization defects in Dmrta2-null model organisms prohibit a clear dissection of a direct role of Dmrta2 in NPC behavior from the secondary effect of an overall reduction in extrinsic hem-derived signals.…”
mentioning
confidence: 99%